Perovskite solar cells: film formation and properties. Issue 17 (7th May 2015) - Song, Tze-Bin; Chen, Qi; Zhou, Huanping; Jiang, Chengyang; Wang, Hsin-Hua; (Michael) Yang, Yang; Liu, Yongsheng; You, Jingbi; Yang, Yang
<x xml:space="preserve">Abstract</x> Perovskite solar cells have received considerable attention in recent years as a promising material capable of developing high performance photovoltaic devices at a low cost.